Comparative study on traditional and modern long span structure / Mohd Fauzi Sukat - Sukat, Mohd Fauzi (2009)
This study was aimed to study about the comparison between traditional and modern long span structure in Malaysia. As we know, a longspan structure extending between supporting structures includes at least two form supports extending between the supporting structures. Usually, long span structure can be classified as large span more than 6m without any support at the centre of structure. Each end of the form support includes a bearing plate coupled to the adjacent supporting structure. In this dissertation, the main objective is to study the advantages and disadvantages of traditional and modern long span structure besides the comparative between time, cost and quality. The area of study is aim in the bridges construction in Malaysia. So, this study will identify types of traditional and modern long span structure beside to compare of both method. Finally, the choosing of the case studies will explain for more detail in the chapter 4.